The skull of Vanzosaura rubricauda (Squamata: Gymnophthalmidae). - Guerra, Cecilia (2009)
A detailed description of the cranial osteology and chondrocranium of Vanzosaura rubricauda is made based both on articulated and partially disarticulated material of dry skeletons and cleared and stained specimens, and are compared with other previously studied gymnophthalmids. Some features of Vanzosaura are interesting, such as the reduction of the supratemporal fenestrae, that may reflect a process of miniaturization, and the fusion of the occipital bones in a single oto-occipital complex with no evident sutures. Based on the anatomical evidence, the skull of Vanzosaura is interpreted as amphikinetic.